Recruiting Strategies to Support the Army's All-Volunteer Force - Orvis, Bruce R. (RAND Corporation, 2016)
The research described in this report was conducted to improve the Army's ability to use recruiting resources and enlistment eligibility policies effectively and efficiently to meet accession requirements under varying recruiting conditions. We assess the cost of meeting enlisted force accession requirements when an optimal mix of television advertising and incentives is feasible or, alternatively, when an incentive-centric strategy is required.